The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10067-017-3887-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes and clinical significance of CD8+CD122+ T cells in the peripheral blood of patients with ankylosing spondylitis

Abstract: The aim of our study was to explore the relationship between circulating T cells and ankylosing spondylitis (AS) and to find the role of the CD8+CD122+ T cells in the pathogenesis and progression of AS. With the method of case-control design, flow cytometry was performed to quantitatively determine the percentage of circulating CD8CD122 T cells in peripheral blood mononuclear cells from established AS patients and age- and gender-matched healthy controls. Serum levels of inflammatory cytokines like interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In 2015, Churland G. et al [61] have found that the proportion of CD8 + Tregs in the peripheral blood of healthy people is less than one-tenth of that of CD4 + Tregs, which makes the study of CD8 + Tregs more difficult. In this study, we found that only one study [21] reported the expression of CD8 + Treg in peripheral blood of patients with AS, and a comprehensive analysis showed that there was a higher proportion of CD8 + Treg in AS group than in the healthy control group. The specific marker, expression, and function of CD8 + Treg need further study.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…In 2015, Churland G. et al [61] have found that the proportion of CD8 + Tregs in the peripheral blood of healthy people is less than one-tenth of that of CD4 + Tregs, which makes the study of CD8 + Tregs more difficult. In this study, we found that only one study [21] reported the expression of CD8 + Treg in peripheral blood of patients with AS, and a comprehensive analysis showed that there was a higher proportion of CD8 + Treg in AS group than in the healthy control group. The specific marker, expression, and function of CD8 + Treg need further study.…”
Section: Discussionmentioning
confidence: 84%
“…To further assess the effect of disease activity, we analyzed 2 studies [9, 21] that reported the proportion of Tregs in active and stable AS patients regardless of the Tregs definitions used (Figure 3). All of these 2 studies used the Ankylosing Spondylitis Disease Activity Score (ASDAS) [4244] to evaluate the disease activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations